Surgical Management of Hidradenitis Suppurativa: Factors Associated with Postoperative Complications and Disease Recurrence. Issue 1 (18th January 2023) - Skorochod, Ron; Margulis, Alexander; Adler, Neta
Abstract : Background: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disorder. Treatment of HS remains challenging, and surgical procedures commonly follow attempts of conservative therapy. To date, a consensus regarding the optimal surgical technique has not been reached, and the implications of conservative therapy on future surgical outcomes have yet to be studied. Methods: A retrospective cohort study of 65 patients surgically treated for HS at a tertiary care center was conducted. Patients' medical records were screened for demographical, clinical, and surgical characteristics. Statistical analysis was conducted to determine associations with postoperative complications and disease recurrence. Results: Fifty patients (75.8%) were treated with systemic antibiotics before opting for surgical resection. Previous treatment with systemic rifampicin was associated with higher rates of postoperative complications ( P = 0.029); however, systemic cephalexin and topical clindamycin were associated with a lower rate of complications ( P = 0.007 and 0.040, accordingly). Medical history of smoking and surgical management with split-thickness skin grafts were associated with higher rates of postoperative complications ( P = 0.012 and 0.014, accordingly). Patients with a greater number of lesions, and those treated with split-thickness skin graft, had higher rates of disease recurrence ( P = 0.0018 and 0.003, accordingly). In a multivariate analysis a greater number of lesions ( P = 0.0498) and the use of autologous split-thickness skin graft ( P = 0.022) were independently associated with higher rates of disease recurrence. Conclusions: Previous conservative medical therapy bears the potential to modulate postoperative outcomes in HS patients, and should be taken into consideration. Despite reports of reliable results with split-thickness skin grafts, we found them to be associated with increased rates of diseases recurrence and postoperative complications.